Kecukupan Asupan Nutrien Asal Hijauan Pakan Kambing PE di Desa Totallang-Kolaka Utara - . Nurlaha; Luki Abdullah; Didid Diapari (Institut Pertanian Bogor, 2015)
This study aimed to identify patterns of feed provision and evaluate the nutritional adequacy of crossbred goats (EC) in Totallang, Lasusua District of North Kolaka. The method used was descriptive analysis to describe the general state of research sites, feeding system and adequacy of nutrien by EC goats. The result revealed that livestock rearing is generally performed by breeders at the age of 1556 years (productive age group) of 81.25 and the remaining 18.75 in those aged >56 years. The experience of breeder ranges from 15 years (68.75) and >6 years (31.25). The type of feed used by farmers in the village of Totallang include: Gliricidia sp., Pennisetum purpureum, Erytrina subumbrans (Hassk.), and Ficus variegata Blume. Gliricidia sp. was dominant forage fed to animals (95.98) and other forage were fed in limited portion such as: pennisetum purpureum (1.79), Erytrina subumbrans (Hassk.) (1.34%) and Ficus variegata Blume (0.89). Gliricidia sp. contributed protein in ration up to 16.82. About 56.25 of farmer fed animal with 100 Gliricidia sp., while 18.75 of farmer used Gliricidia sp. in combination with Erytrina subumbrans (Hassk.) and 12.5 of them fed EC goats with combination of Gliricidia sp. and Erytrina subumbrans (Hassk.) or and Ficus variegata Blume. About 62.5 farmer in Totallang fed their goat with sufficient dry matter intake according to Kearl (1982), as well as 100 of goat were sufficient in crude protein intake meanwhile TDN intake were not fulfilled by farmer about 93.75.